INTEGRATION OF CIVIC EDUCATION INTO LOWER-SECONDARY SCHOOL CURRICULUM - Marsone, Stanislava (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
There have been dramatic changes in the concepts of democracy in European countries and throughout the world, which have led to the changes in attitudes between a person and a society. Globalisation has brought the culture of stereotypes, multicultural society, migration – these are only some aspects that indicate the growth of importance of civic education at every level of education in the modern world. To choose the most effective methods and forms of civic education, it is essential to analyse world experience and cultural traditions of every country, which are based on the ideals and values, and are the fundament of educational traditions. The aim of this article is to analyse the presence of civic education elements in the lower-secondary school curriculum, and to evaluate the possibilities of possible improvements.